Biological correlates of treatment resistant depression: a review of peripheral biomarkers - Mancuso, Emiliana; Sampogna, Gaia; Boiano, Alessia; Della Rocca, Bianca; Di Vincenzo, Matteo; Lapadula, Maria Vita; Martinelli, Flavia; Lucci, Federico; Luciano, Mario (Frontiers in Psychiatry, 2023)
Introduction: Many patients fail to respond to multiple antidepressant interventions, being defined as "treatment-resistant depression" (TRD) patients. TRD is usually associated with increased severity and chronicity of symptoms, increased risk of comorbidity, and higher suicide rates, which make the clinical management challenging. Efforts to distinguish between TRD patients and those who will respond to treatment have been unfruitful so far. Several studies have tried to identify the biological, psychopathological, and psychosocial correlates of depression, with particular attention to the dysfunction of the inflammatory system.In this paper we aim to review available studies including blood-based samples testing the full range of biomarkers in TRD patients in order to reshape TRD definition and improve its diagnosis, treatment, and prognosis.We searched the most relevant medical databases and included studies reporting original data on possible biomarkers of TRD. The keywords "treatment resistant depression" or "TRD" matched with "biomarker", "inflammation", "hormone", "cytokine" or "biological marker" were entered in PubMed, ISI Web of Knowledge and SCOPUS databases. Articles were included if they included a comparison with healthy controls (HC).Results: Of the 1878 papers identified, 35 were included in the present study. Higher plasma levels of IL-6 and TNF-α were detected in TRD patients compared to HC. While only a few studies on cortisol have been found, four papers showed elevated levels of C-reactive protein among these patients and four articles focused on immunological cells. Altered kynurenine metabolism in TRD patients was reported in two studies, while contrasting results were found with regard to BDNF.Only a few biological alterations correlate with TRD. TNF-α seems to be the most relevant biomarker to discriminate TRD patients from both HC and treatment-responsive MDD patients. Moreover, several discrepancies among studies have been found, due to methodological differences and the lack of a standardized diagnostic definition of TRD.